Effects of the Family Nurse Partnership on all eligible mothers: a data linkage cohort study in England. - Katie Harron; Francesca Cavallaro; Jan van der Meulen; Eilis Kennedy; Ruth Gilbert (PLoS ONE)
Background An intensive programme of home visiting, the Family Nurse Partnership (FNP), is received by around one in four first-time adolescent mothers in selected areas in England. During home visits, nurses support mothers to make choices about healthy pregnancies, improving child development, and fulfilling their own aspirations and ambitions. Evidence is needed of the wider effects of the FNP, including for mothers not enrolled in the programme (who might experience unintended effects). We evaluated child and maternal outcomes for all eligible mothers giving birth before, during, and after the period in which FNP was active in local areas. Methods We created a linked cohort of 237,185 eligible mothers, aged 13-19, who gave birth between April 2010 and March 2019, and who had a first antenatal booking appointment (or a date of 28 completed weeks of gestation, if missing) when FNP was active in their area. We used administrative hospital data to identify unplanned maternal/child hospitalisations up to 2 years after birth for children born and mothers delivering before, during and after FNP was active. Generalised linear models were used to adjust for background regional time trends, maternal characteristics, and clustering of outcomes within residential areas. Results We found no evidence of differences in unplanned hospital admissions for children born during the FNP period (36.9% versus 36.0%, relative risk [RR] 1.01; 95% CI 0.99-1.02), or after FNP was active (37.1%, RR 1.0; 95% CI 0.95-1.06), compared with those born before FNP was active. There was no evidence of differences in child admissions for maltreatment/injury-related diagnoses or for maternal admissions for adversity-related diagnoses. Conclusion Child and maternal outcomes were similar before, during and after FNP active periods, suggesting that the FNP did not have a wider impact on outcomes in all eligible mothers, including those not participating in the FNP.